Development and Optimization of an ELISA to Quantitate C3(H2O) as a Marker of Human Disease - Elvington, Michelle; Liszewski, M. Kathryn; Liszewski, Alexis R.; Kulkarni, Hrishikesh S.; Hachem, Ramsey R.; Mohanakumar, Thalachallour; Kim, Alfred H. J.; Atkinson, John P. (Frontiers in Immunology, 2019)
Discovery of a C3(H2O) uptake pathway has led to renewed interest in this alternative pathway triggering form of C3 in human biospecimens. Previously, a quantifiable method to measure C3(H2O), not confounded by other complement activation products, was unavailable. Herein, we describe a sensitive and specific ELISA for C3(H2O). We initially utilized this assay to determine baseline C3(H2O) levels in healthy human fluids and to define optimal sample storage and handling conditions. We detected 500 ng/ml of C3(H2O) in fresh serum and plasma, a value substantially lower than what was predicted based on previous studies with purified C3 preparations. After a single freeze-thaw cycle, the C3(H2O) concentration increased 3- to 4-fold ( 2000 ng/ml), subsequent freeze-thaw cycles had a lesser impact on C3(H2O) generation. Further, we found that storage of human sera or plasma samples at 4C for up to 22 h did not generate additional C3(H2O). To determine the potential use of C3(H2O) as a biomarker, we evaluated specimens from patients with inflammatory-driven diseases. C3(H2O) concentrations were moderately increased (1.5- to 2-fold) at baseline in sera from active systemic lupus erythematosus (SLE) and rheumatoid arthritis (RA) patients compared to healthy controls. In addition, upon challenge with multiple freeze-thaw cycles or incubation at 22 or 37C, C3(H2O) generation was significantly enhanced in SLE and RA patients’ sera. In bronchoalveolar lavage fluid from lung-transplant recipients, we noted a substantial increase in C3(H2O) within 3 months of acute antibody-mediated rejection. In conclusion, we have established an ELISA for assessing C3(H2O) as a diagnostic and prognostic biomarker in human diseases.